Export Competitiveness Analysis of Indonesian Shoe Commodities in the International Market - Rizqi Muttaqin; Denny Saputera; Aditya Yudanegara (Transpublika Publisher, 2025)
Indonesia is one of the countries that produces good quality shoe producers in the world, many of whose production is exported. The purpose of this study is to analyze the competitive position and performance of shoes production in Indonesia as an export product. Shoes product is selected as a reason to the demand from abroad for which is increasing from year to year. The data used in this study is panel data on shoe exports over a period of ten years, namely from 2012-2022 by analyzing top ten export destination countries, namely the United States, Belgium, China, Germany, Japan, the Netherlands, England, South Korea, Italy, Mexico. The Revealed Comparative Advantages (RCA) and Export Product Dynamics (EPD) methods are used respectively to analyze the comparative advantages and performance of shoe exports from Indonesia. The results of the study show that Indonesia has a comparative advantage based on the RCA method, then based on the EPD method, it is obtained that Indonesian sports shoes are classified as rising star in ten export destination countries, Australia, Belgium, China, Germany, Japan, South Korea, Mexico, Netherlands, England and United States. The research found that Belgium has the most competitive to be an export destination with RCA Value 93.7 despite the total export value in modest conditions. The lowest RCA value is Japan 2.08 despite high volume in total exports.